Performativitas Gender Selebriti Instagram Queer Pada Masyarakat Jakarta Selatan (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This study aims to describe, dissect, and analyze more deeply the gender performativity of queer Instagram celebrities (Selebgram) in the people of South Jakarta. This study uses a qualitative approach with an explanatory type. The explanatory qualitative research method aims to provide a detailed description of gender performativity carried out by queer celebrities on Instagram social media, as well as the views of the people of South Jakarta on celebrity gender performativity on Instagram social media. The results of the study show that performativity is a statement made by queer Instagram celebrities using Instagram social media. Selebgrams display various uploaded contents. Personified posts aim to provide education about gender other than heterosexual. This display seeks to express the gender of Celebgrams individually. The people of South Jakarta in this study showed their acceptance of the performance of queer celebrities. Some of Selebgram's queer content uploaded was used as a reference by a start-up employee in South Jakarta. Some workers and students like the appearance of queer celebrities. It can be suggested by the community to reduce the focus on gender personification, and open their minds to the rights and freedoms of each gender. Keywords: Instagram, Heteronormativity, Performativity, Celebgram, Queer